GELARAN FASHION SHOW “KAWULA MUDA FESTIVAL (TEMA GELORA WASTRA)” SEBAGAI WUJUD APRESIASI BERKARYA - Aninda Dyah Hayu Pinasti Putri (Canthing, 2025)
This community service initiative aimed to provide a platform for appreciation and creative expression for young designers, fashion vocational high school students, and fine arts academy students through a fashion show titled "Kawula Muda Festival (Gelora Wastra Theme)." The event was held at Pendhapi Balaikota Surakarta on February 10, 2024, coinciding with the Chinese New Year celebration, which attracted many visitors. The activities included a beauty class, an art workshop, and a fashion show featuring the works of young designers with traditional fabric themes. This event benefited not only the designers but also other stakeholders such as photographers, makeup artists, and models who needed portfolios and experience. The results showed increased confidence among participants, public enthusiasm, and requests for similar activities to be held continuously. This fashion show serves as a concrete form of support for the regeneration and development of the creative industry, particularly in local wisdom-based fashion design. Keywords: fashion show, young designers, community service, traditional fabric, appreciation of work